The Pakistan Brain Tumour Epidemiology Study - Syed Ather Enam; Mashal Murad Shah; Mohammad Hamza Bajwa; Muhammad Usman Khalid; Saqib Kamran Bakhshi; Erum Baig; Iqbal Azam Altaf; Altaf Ali Laghari; Saad bin Anis; Naveed Zaman Akhunzada; et al. (Journal of the Pakistan Medical Association, 2022)
Objective: To provide information about brain tumour epidemiology in Pakistan and potential associated risk factors due to family, medical and social characteristics. Methods: A retrospective cross-sectional nationwide study was designed by the Pakistan Society of Neuro-oncology, to include patients diagnosed with brain tumours in Pakistan retrospectively, from January 1, 2019- December 31, 2019. The study intended to involve data from all age groups for all brain tumour cases, irrespective of histopathology which would determine the national prevalence and incidence of these tumours. Results: A total of 2750 brain tumour cases were recorded, of which 1897 (69%) were diagnosed in the public sector. MRIs were a more common radiological study compared to CT scans. Gliomas were the most common tumours 778 (28.29%), while pineal tumours were the least common 19 (0.69%). The median age at diagnosis for males was 36 (24-49), while the median age at diagnosis for females was 37 (24-48). Hypertension was the most common co-morbidity in patients diagnosed with a brain tumour, 524 (51.89%), and smoking was the most frequent social behaviour, 355 (62.02%). Findings indicate a low metastasis frequency and few females seeking care. Conclusion: The PBTES and the PBTC have presented an opportunity and platform for hospitals and health professionals to work together to strengthen cancer care health systems, ensure implementation of treatment guidelines and conduct regular cancer registration. Keywords: brain neoplasms, registries, retrospective studies, epidemiology, Neuro-oncological surgery. Continue...